Migration as a substitute for informal activities: Evidence from Tajikistan - Ilhom Abdulloev; Ira N. Gang; John Landon-Lane (Osteuropa-Institut Regensburg, 2011)
How is migration related to informal activities? They may be complementary since new migrants may have difficulty finding employment in formal work, so many of them end up informally employed. Alternatively, migration and informality may be substitutes since migrants' incomes in their new locations and income earned in the home informal economy (without migration) are an imperfect trade-off. Tajikistan possesses both a very large informal sector and extensive international emigration. Using the gap between household expenditure and income as an indicator of informal activity, we find negative significant correlations between informal activities and migration: the gap between expenditure and income falls in the presence of migration. Furthermore, Tajikistan's professional workers ability to engage in informal activities enables them to forgo migration, while low-skilled non-professionals without post-secondary education choose to migrate instead of working in the informal sector. Our empirical evidence suggests migration and informality substitute for one another.
Keywords: O17; J61; P23; 330; informal; migration; remittances; Tajikistan; Internationale Wanderung; Auswanderung; Informeller Sektor; Rücküberweisung (Migranten); Tadschikistan